2015
DOI: 10.1021/acs.jmedchem.5b00426
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of (+)-Naltrexone-Inspired Toll-like Receptor 4 (TLR4) Antagonists

Abstract: Activation of Toll-like receptors has been linked to neuropathic pain and opioid dependence. (+)-Naltrexone acts as a Toll-like receptor 4 (TLR4) antagonist and has been shown to reverse neuropathic pain in rat studies. We designed and synthesized compounds based on (+)-naltrexone and (+)-noroxymorphone and evaluated their TLR4 antagonist activities by their effects on inhibiting lipopolysaccharide (LPS) induced TLR4 downstream nitric oxide (NO) production in microglia BV-2 cells. Alteration of the N-substitue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…The lead opioid in this study was also tested in vivo in a Hargreaves assay, and was able to demonstrate efficacy as compared to a morphine/vehicle [30] .…”
Section: Tlr4-mediated Neuroinflammationmentioning
confidence: 99%
“…The lead opioid in this study was also tested in vivo in a Hargreaves assay, and was able to demonstrate efficacy as compared to a morphine/vehicle [30] .…”
Section: Tlr4-mediated Neuroinflammationmentioning
confidence: 99%
“…As shown in Fig. 2A, (+)-1 inhibited LPS-induced TLR4 signaling of NO in a concentration-dependent manner, with an IC 50 of 4.7 6 1.8 mM, which possesses ;25 times better TLR4 antagonist activity than (+)-naltrexone (105.5 6 10.1 mM) (19,21). In addition to NO inhibition, (+)-1 also inhibited the LPS-induced TLR4 signaling of proinflammatory factors TNF-a (IC 50 = 12.1 6 2.0 mM, Fig.…”
Section: Results (+)-1 Enantioselectively Inhibits Tlr4 Signalingmentioning
confidence: 84%
“…However, the TLR4 antagonist activity of (+)-naltrexone was moderate [half maximal inhibitory concentration (IC 50 ) = 105.5 6 10.1 mM], and it is not long acting (19), which severely prevents its wide in vivo application. Structure-activity relationship studies of (+)-naltrexone showed that the substituted group at N-17 affected the binding with MD-2 and TLR4 antagonistic activity, increasing the hydrophobicity of the substituent at N-17 and improving its TLR4 antagonistic activity (19,20). However, it should be noted that increasing the hydrophobicity of substituted groups meanwhile compromised the drug likeness of (+)-naltrexone-inspired TLR4 antagonists.…”
mentioning
confidence: 99%
“…In discrete ‘low-doses’ ranging from 1 to 5 mg, naltrexone acts as a glial modulator [14,15]. It specifically binds to Toll-like receptor 4, where it acts as an antagonist [8,16,17]. Toll-like receptor 4 downstream cellular signaling includes myeloid differentiation primary response 88 (MyD88) and toll-interleukin receptor (TIR)-domain-containing adapter-inducing interferon-β (TRIF) pathways, both ultimately leading to inflammatory end-products such as interleukin (IL)-1, tumor necrosis factor (TNF)-α, interferon-β, and nitric oxide [18].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Low-dose naltrexone disrupts the TRIF portion of the signaling cascade which reduces TNF-α and interferon-β synthesis [8]. Consequently, activated microglial cells expressing Toll-like receptor 4, otherwise a non-constitutive receptor, exert an attenuated pro-inflammatory profile [16]. The span and importance of neuronal Toll-like receptor 4 signaling is still under debate with ex vivo [19] and in vitro [20] investigations emphasizing its role in neuroinflammation, a role traditionally reserved for glia in the central nervous system (CNS) [21].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%